Sex-Specific Differences in the Association of Metabolically Healthy Obesity With Hyperuricemia and a Network Perspective in Analyzing Factors Related to Hyperuricemia - Tian, Simiao; Liu, Yazhuo; Feng, Ao; Zhang, Shulong (Frontiers in Endocrinology, 2020)
Keywords: metabolic health, obesity, hyperuricemia, sex-specific effect, bayesian networks.Background: Although obesity is a well-known risk factor for hyperuricemia, it remains unclear whether obese subjects with metabolically healthy status have a decreased the risk of hyperuricemia and whether sex modifies the association of MHO with hyperuricemia risk. We aimed to investigate the sex-specific association between MHO and other obesity phenotypes and hyperuricemia, and to use Bayesian networks to determine and visualize the interactions among hyperuricemia and its related factors.